PROTECTIVE EFFECTS OF γ -AMINOBUTYRIC ACID (GABA) ON THE SMALL INTESTINAL MUCOSA IN HEAT-STRESSED WENCHANG CHICKEN - Z. Chen; J. Xie; M. Y.Hu; J. Tang; Z. F. Shao; M. H. Li (Journal of Animal and Plant Sciences, 2015)
We explored the effects of heat stress (HS) and γ-aminobutyric acid (GABA) treatment on the structure and development of small intestinal mucosa in Wenchang chicken. One-day old male Wenchang chickens were randomly divided into control group (CK), heat stress group (HS) and GABA+HS group. The chickens from GABA+HS group were fed with 0.2 ml 0.5% GABA solution daily. In addition, the chicken from HS and GABA+HS groups were subjected to heat stress treatment at 40 ±0.5°C for 2h during 13:00-15:00 every day. Results showed that compared with CK group, HS group exhibited marked decline in villus length, mucosa thickness, intestinal wall thickness, and crypt depth in duodenum and ileum, and significantly fewer goblet cells (P<0.05). In contrast, compared with HS group, GABA+HS group exhibited enhanced villus length, mucosa thickness, intestinal wall thickness, and crypt depth in duodenum and ileum, as well as a much higher number of goblet cells (P<0.05). Therefore, heat stress caused significant structural damages to chicken small intestinal mucosa, and markedly reduced the number of goblet cells. GABA showed protective effects to alleviate HS-induced damages of the intestinal mucosa and increased the number of goblet cells.
Keywords: GABA; heat stress; small intestinal mucosa; Wenchang chicken